A Protein Inventory of Human Ribosome Biogenesis Reveals an Essential Function of Exportin 5 in 60S Subunit Export - Wild, Thomas (Public Library of Science, 2010)
The assembly of ribosomal subunits in eukaryotes is a complex, multistep process so far mostly studied in yeast. In S. cerevisiae, more than 200 factors including ribosomal proteins and trans-acting factors are required for the ordered assembly of 40S and 60S ribosomal subunits. To date, only few human homologs of these yeast ribosome synthesis factors have been characterized. Here, we used a systematic RNA interference (RNAi) approach to analyze the contribution of 464 candidate factors to ribosomal subunit biogenesis in human cells. The screen was based on visual readouts, using inducible, fluorescent ribosomal proteins as reporters. By performing computer-based image analysis utilizing supervised machine-learning techniques, we obtained evidence for a functional link of 153 human proteins to ribosome synthesis. Our data show that core features of ribosome assembly are conserved from yeast to human, but differences exist for instance with respect to 60S subunit export. Unexpectedly, our RNAi screen uncovered a requirement for the export receptor Exportin 5 (Exp5) in nuclear export of 60S subunits in human cells. We show that Exp5, like the known 60S exportin Crm1, binds to pre-60S particles in a RanGTP-dependent manner. Interference with either Exp5 or Crm1 function blocks 60S export in both human cells and frog oocytes, whereas 40S export is compromised only upon inhibition of Crm1. Thus, 60S subunit export is dependent on at least two RanGTP-binding exportins in vertebrate cells.